2015 IEEE 26th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC) 2015
DOI: 10.1109/pimrc.2015.7343455
|View full text |Cite
|
Sign up to set email alerts
|

Efficient selection of user sets for downlink non-orthogonal multiple access

Abstract: Non-orthogonal multiple access (NOMA), which uses superposition coding at the transmitter side and successive interference cancellation at the receiver side, is a promising new downlink multiple access scheme. The product of user average throughputs among all users within a cell can be maximized by optimal proportional fair (PF) scheduling, but this is computationally complex because it requires an exhaustive search for all possible user sets and optimal power allocation among users. In this work, we propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…As (28) indicates, the available scheduling factor of every valid pair of users can be computed, and the largest one can be selected. A similar user set-selection algorithm is formulated based on the mathematical characteristics of the PF metric [44]. This method can also reduce the computational complexity by judging whether a user set is worth multiplexing based on a simple condition between the weakest two users within the set.…”
Section: ( ) ( ) ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…As (28) indicates, the available scheduling factor of every valid pair of users can be computed, and the largest one can be selected. A similar user set-selection algorithm is formulated based on the mathematical characteristics of the PF metric [44]. This method can also reduce the computational complexity by judging whether a user set is worth multiplexing based on a simple condition between the weakest two users within the set.…”
Section: ( ) ( ) ( )mentioning
confidence: 99%
“…An encouraging extension of the UPPA scheme would be a power allocation scheme in the multi-user NOMA system where the scheduler allows more than two users. Also, it requires more research in order to apply UPPA schemes and variations [44] to a practical system with a suitable modulation and coding scheme. …”
Section: A Dynamic User Pairingmentioning
confidence: 99%
“…The throughputs of the conventional and proposed schemes are evaluated with CCC through Monte Calro simulation [16]. Proportional fairness (PF) scheduling is applied and the time interval of the PF scheduling is set to 100 [21]. The number of resource blocks (RBs) is 24 and the number of subcarriers in one RB is 12.…”
Section: System-level Aspectmentioning
confidence: 99%
“…In [62], pre-defined user grouping and fixed per-group power allocation is proposed to reduce the overhead associated with power allocation signaling while maintaining a hefty portion of NOMA gains. The complexity reduced proportional fair scheduling method for NOMA is proposed in [63]. It was shown that by searching only the user combinations that are worth non-orthogonally-multiplexing, the number of the user combinations to be searched can be significantly reduced while keeping almost identical average and celledge throughput performance compared with conventional exhaustive search method.…”
Section: Advanced Modulation and Multiple Access Schemesmentioning
confidence: 99%